Akibat Hukum Pembatalan Perjanjian Jual Beli Rumah di Alam Sutera Akibat Wanprestasi: Perspektif Hukum Perdata - Agussoesanto, Debhie; Famulia, Ledy (Diktum: Jurnal Ilmu Hukum, 2026)
Alam Sutera independent township due to default. The rapid growth of the property sector This research is motivated by the frequent practice of house sale and purchase transactions in the elite Alam Sutera area, which is often not accompanied by adequate legal understanding regarding the risks of default, particularly when the house certificate turns out to be still used as bank loan collateral. The study aims to examine the legal construction of agreement cancellation under the Indonesian Civil Code and the legal consequences arising from default on the rights and obligations of the parties. The method used is normative legal research with statutory and conceptual approaches, supported by descriptive-qualitative analysis. The findings reveal two specific results. First, although Article 1266 of the Civil Code requires that cancellation of a reciprocal agreement be sought through a court decision, in practice at Alam Sutera, the freedom of contract principle (Article 1338 of the Civil Code) is frequently invoked to include clauses waiving such requirement, thereby allowing unilateral cancellation by means of a formal notice (somasi). Second, the legal consequence of cancellation not only mandates the full return of the down payment but also imposes compensation for costs, losses, and interest (Articles 1243–1246 of the Civil Code) proportionally based on proof of actual damages, not automatically double the amount. This study concludes that a balance between legal certainty for developers and consumer protection must be enforced by limiting unilateral waiver clauses of Article 1266. Practically, consumers are advised to scrutinize resolutive condition clauses in the PPJB before signing the agreement.